2006
DOI: 10.1111/j.1600-0625.2006.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor‐β expression in melanocytic lesions

Abstract: Melanomas rarely occur before puberty, have a higher death rate for males, and tend to be more invasive during pregnancy. Prior to the discovery of a second oestrogen receptor (ERbeta), studies with the initial oestrogen receptor, ERalpha, showed no obvious role for oestrogen in the pathophysiology of benign or malignant melanocytic lesions. To investigate the specific immunostaining patterns of ERalpha and ERbeta, benign nevocytic nevi, dysplastic nevi with mild, moderate and severe cytological atypia, lentig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(161 citation statements)
references
References 55 publications
(82 reference statements)
7
151
1
2
Order By: Relevance
“…Interestingly, in our study women presented at an earlier mean age than their male counterparts and this difference was statistically significant (p = 0.03). This finding may be explained by the fact that in women the incidence of melanomas is highest during the childbearing age and there is a drop around menopause (Schmidt, Nanney, & Boyd, 2006). The mean age in our female population was 50 years and this may have influenced the lower proportion of melanomas seen in our patient population.…”
Section: Discussioncontrasting
confidence: 44%
“…Interestingly, in our study women presented at an earlier mean age than their male counterparts and this difference was statistically significant (p = 0.03). This finding may be explained by the fact that in women the incidence of melanomas is highest during the childbearing age and there is a drop around menopause (Schmidt, Nanney, & Boyd, 2006). The mean age in our female population was 50 years and this may have influenced the lower proportion of melanomas seen in our patient population.…”
Section: Discussioncontrasting
confidence: 44%
“…Also in melanoma, ERβ expression levels are inversely related to primary cancer progression in both men and women 93 and, in a mouse model of the disease, tamoxifen treatment significantly inhibited metastatic spread in female animals 94 .…”
Section: Sex Hormone Signaling In Specific Cancer Typesmentioning
confidence: 99%
“…Numerous studies have attempted to identify a role for ERα as a biomarker in melanoma (Tanemura et al, 2007), in the way that ERα serves as a prognostic marker in breast cancer (Miller, 1996), but to date this has been without clear success and the spurious distribution of ERα in melanoma cells has obscured the role of oestrogen in melanoma. However, recent studies show that ERβ, and not ERα, is the predominant oestrogen receptor type in melanocytic lesions, with ERβ being detected ubiquitously where ERα was not (Schmidt et al, 2006). The discovery that ERβ immunoreactivity was increased in severely dysplastic nevi and lentigo malignas (in-situ melanoma) but decreased in melanomas progressively deeper in the dermis suggests that ERβ may be playing a role in the biology of these cancers and might serve as a useful prognostic marker (Schmidt et al, 2006).…”
Section: Parabens and Skin Cancermentioning
confidence: 99%
“…Melanoma affects younger people more than most cancers, with about 40% of cases in the under 50s (Gavin and Walsh, 2005), and there is currently a striking increase in incidence in youth (Strouse et al, 2005;Downard et al, 2007) and a strong inverse relationship with social deprivation (Gavin and Walsh, 2005). The natural history of human malignant melanoma has suggested that oestrogen might in½uence the incidence and development of these tumours (Schmidt et al, 2006), partly because the incidence in females is low before puberty, rising steeply through the reproductive years (Strouse et al, 2005), and survival may vary between men and women (Reintgen et al, 1984;Gavin and Walsh, 2005). Numerous studies have attempted to identify a role for ERα as a biomarker in melanoma (Tanemura et al, 2007), in the way that ERα serves as a prognostic marker in breast cancer (Miller, 1996), but to date this has been without clear success and the spurious distribution of ERα in melanoma cells has obscured the role of oestrogen in melanoma.…”
Section: Parabens and Skin Cancermentioning
confidence: 99%